ELECTORAL SYSTEM AND POLITICAL STABILITY: IMPLICATIONS FOR PEOPLE'S WELFARE - Era Purike (Adisam Publisher, 2025)
The electoral system plays a vital role in determining the quality of a country's political governance and stability, which in turn affects the welfare of the people. The choice of system, whether proportional, majoritarian, or mixed, has implications for political representation and the accountability of the elected government. An effective system encourages political stability by ensuring fair representation and a non-centralised distribution of power. Strong political stability allows the government to focus on sustainable development policies, create a healthy investment climate, and improve public services, all of which are important for the welfare of the community. However, stability must be in harmony with inclusiveness so as not to marginalise certain groups and maintain the essence of democracy. The balance between political stability and inclusiveness is the key to ensuring sustainable development and equitable welfare across all levels of society.